Prenatal diagnosis and outcome of unilateral multicystic kidney. (3rd October 2021) - Turkyilmaz, Gurcan; Cetin, Bilal; Erturk, Emircan; Sivrikoz, Tugba; Kalelioglu, Ibrahim; Has, Recep; Yuksel, Atıl; Oktar, Tayfun; Ziylan, Orhan
Abstract: We reviewed the records of 144 patients. The mean gestational age at first US diagnosis was 27.5 ± 4.3 weeks. An anomaly of the contralateral kidney was detected in 25% of cases. An extrarenal anomaly was detected in 13.8%. Karyotype analysis was performed in 16.6% of cases and revealed trisomy 18 in 2 cases with extrarenal defects. Karyotype analysis was normal in all the patients who had isolated multicystic dysplastic kidney (MCDK). The diagnostic accuracy of prenatal ultrasound was 92.2%. Contralateral kidney anomaly was detected 33.9% of patients, and half of these were vesicoureteral reflux. Antihypertensive therapy was required in 2.6% of cases. Nephrectomy was performed in 8%, and partial or total involution of MCDK was achieved in 33.9% of patients. MCDK can be accurately diagnosed by prenatal sonography, and prognosis depends on extrarenal and contralateral renal abnormalities. In isolated cases, require of surgery is rare, and serial follow-up is suggested to determine involution. Impact statement: What is already known on this subject? Multicystic dysplastic kidney (MCDK) is one of the most renal anomalies and is associated with numerous renal and extrarenal abnormalities. It can lead to severe consequences in the neonatal period. What do the results of this study add? The accuracy of prenatal ultrasonography is excellent for detecting MCDK. In isolated unilateral cases, chromosomal aberrations are low, and the majority of them involute spontaneously. A periodic follow-up of the contralateral kidney is mandatory due to an increased risk of an anomaly. Genital anomaly risk is increased in males. What are the implications of these findings for clinical practice and/or further research? Detailed evaluation and follow-up of the contralateral kidney are crucial for counselling in isolated cases. Karyotype analysis in isolated unilateral MCDK is debateable. Postnatal prognosis is encountering, and the majority of patients have no requirement of surgery.